Facing Reciprocity: How Photos and Avatars Promote Interaction in Micro-communities - Timm Teubner; Sonia Camacho (Group Decision and Negotiation, 2023)
Online platforms facilitate the formation of micro-communities on the Internet by enabling exchange between locally dispersed individuals. Since all interactions are mediated through the online platform, user representation plays a critical role for such communities. Grounded in Social Exchange Theory, we report results of a behavioral experiment on the role of user profile photos and avatars for the emergence of network structures over time. While overall network value increases slightly, the underlying structures of exchange shift systematically from many weak ties to fewer but significantly stronger reciprocal exchange relations. Interestingly, despite representing users in a highly abstracted way, avatars yield outcomes comparable to those when using actual photographs. We discuss theoretical and practical implications of how online platforms can leverage social cues such as profile photos and avatars to manage and support micro-communities.
Keywords: C9; D61; D85; D91; 650; Laboratory experiment; Micro-communities; Reciprocity; Social cues; Social exchange theory